Teaching for Diversity. Model for the Implementation of the Sexual and Gender Diversity Perspective in Educational Institutions - Vázquez Parra, José Carlos (2022)
Educational inclusion refers to the set of actions and processes that institutions carry out to offer equal opportunities for all their students, regardless of their characteristics. This article raises the need for educational institutions to commit to diversity by adopting a sexual and gender diversity perspective, through the proposal of an implementation model. In conclusion, this model outlines a roadmap for inclusion, providing a useful tool for the development of policies and actions focused on diversity and the respect and inclusion of LGBTIQA+ people in the educational community.